Who's buying entertainment (Who's buying series., 2015)
The eleventh edition of Who's Buying Entertainment is based on unpublished data collected by the Bureau of Labor Statistics' 2013 Consumer Expenditure Survey-you can't get these data online. It examines how much Americans spend on amusing themselves by the demographics that count: age, income, high-income households, household type, race and Hispanic origin, region of residence, and education. To round out the spending picture, it also presents who-are-the-best-customers analyses of the data, showing the demographics of the best and biggest customers at a glance. The individual products and services examined in this report include items ranging from television sets to movie tickets, video games, cable service, pet food, toys, sports equipment, and recreational vehicles.